Pemberian Nafkah - Rohim, M. Yusuf Nur; Ridwan, Muh. Saleh; M, Misbahuddin (Madani: Jurnal Ilmiah Multidisiplin, 2024)
This article discusses livelihood from an Islamic perspective. Islamic Sharia pays special attention to women, more specifically regarding women's rights to receive a living. There are so many arguments from the Koran and Hadith that indicate the obligation to fulfill women's right to support. Islamic Sharia regulates the rights and obligations between husband and wife after the marriage contract takes place. The husband's support for his wife is one of the obligations caused by the marriage contract. The research method used in preparing this article is a descriptive study by explaining the definition, type, size, legal basis for livelihoods and the laws that regulate this matter, which were researched through reading materials including books, statutory regulations and various other related sources.